POTENSI WISATA ALAM DI DESA NUPABOMBA KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Indris, Feby Fitria; Mallombasang, Sri Ningsih; Sustri, Sustri (Universitas Tadulako, 2018)
Nupabomba Village is one of the villages that is quite strategic and has the potential of natural tourist attraction objects, besides having the potential of natural tourist attraction objects (ODTWA) the area also has a rich diversity of flora and fauna, waterfalls, customs, rivers, rocks and natural phenomena that can support the development of tourist attractions. The purpose of this study was to determine the feasibility of natural tourism potential in Nupabomba Village, Tanantovea District, Donggala Regency as a tourist destination. This research was conducted in Nupabomba Village, Tanantovea District, Donggala Regency, Central Sulawesi Province, for two months, from August to October 2017. This study used descriptive methods to obtain all forms of data and information that could support the preparation of research reports, survey methods by observing direct field work accompanied by interviews with the community, community leaders and village officials in the context of collecting data and information, the method of documentation by conducting data collection techniques by documenting sources in the field relating to the problem being investigated, while the data analysis used is a guideline Analysis of the Regional Nature Tourism Attraction and Attraction Operations (ADO-ODTWA) of the Director General of PHKA 2003 in accordance with the values determined for each criterion. The results of the study show that the assessment using ADO-ODTWA of the natural potential in Nupabomba Village, Tanantovea District, Donggala Regency, deserves to be made as a tourist destination with the feasibility level achieved based on the eligibility criteria of each element / sub-criteria such as attractiveness, accessibility, and facilities and supporting infrastructure that is equal to 86. 875% of the total assessment of elements / sub criteria which means the village is worthy of being used as a tourist destination. But there are some supporting facilities and infrastructure that need to be added in order to increase the attractiveness of tourists.